2022
DOI: 10.3390/foods11070949
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Ganoderic Acids from Ganoderma lucidum Fruiting Body on Alcoholic Liver Injury and Intestinal Microflora Disturbance in Mice with Excessive Alcohol Intake

Abstract: This study aimed to investigate the protective effects of ganoderic acids (GA) from Ganoderma lucidum against liver injury and intestinal microbial disorder in mice with excessive alcohol intake. Results showed GA supplement significantly inhibited the abnormal elevation of the liver index, serum lipid parameters, aspartate aminotransferase and alanine aminotransferase in mice exposed to alcohol intake, and also significantly protected the excessive lipid accumulation and pathological changes. Alcohol-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 85 publications
1
9
1
Order By: Relevance
“…In our study, we observed that DBTVS significantly decreased serum TC, TG, and LDL‐C, which is consistent with the results for liver oil red O staining (Figure 2 ). However, it is worth noting that our study also revealed a reduction in HDL‐C levels following DBTVS administration, which contradicts the findings of some other studies (Cao et al., 2022 ; Guo, Zhu, et al., 2022 ; Lin et al., 2021 ). Previous beliefs considered HDL‐C as a “good cholesterol,” which seems to prevent the development of atherosclerotic disease.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we observed that DBTVS significantly decreased serum TC, TG, and LDL‐C, which is consistent with the results for liver oil red O staining (Figure 2 ). However, it is worth noting that our study also revealed a reduction in HDL‐C levels following DBTVS administration, which contradicts the findings of some other studies (Cao et al., 2022 ; Guo, Zhu, et al., 2022 ; Lin et al., 2021 ). Previous beliefs considered HDL‐C as a “good cholesterol,” which seems to prevent the development of atherosclerotic disease.…”
Section: Discussioncontrasting
confidence: 99%
“…The intestinal flora structure in the AG group demonstrated significant alterations in both the small and large intestines compared to that of the CG group. These observations align with the findings of Cao et al’s study [ 36 ]; however, the effect of alcohol on the intestinal flora structure was greater in the small intestine. The structure of the intestinal flora in the small intestine in the HG group recovered to resemble that in the CG group following the administration of high-dose LCJ.…”
Section: Resultssupporting
confidence: 92%
“… [73] . In another report, the active ingredient Ganoderma acids significantly reduced the level of pathogenic bacteria Helicobacter and exerted liver protection by regulating liver lipid metabolism by increasing the Lactobacillus , Faecalibaculum , and Romboutsia [74] . Although the opposite result was shown in Lv's work, the Lactobacillus level was reduced [75] , which may be because the excessive abundance of Lactobacillus also disturbs lipid metabolism in the liver [76] .…”
Section: Medicine Food Homology Species Treat Diseases By Regulating ...mentioning
confidence: 93%